Minority paradoxes: ethnic differences in self-reported offending and official crime statistics - Leerkes, Arjen (The British journal of criminology, 2019)
Immigrants and their native-born children tend to be overrepresented among crime suspects in Europe. Using a representative Dutch survey, we examine whether inhabitants of Turkish and Moroccan origin also self-report more crimes than the native Dutch. In addition, we test various explanations for ethnic differences in crime, partly using variables that are unavailable in administrative data (socio-economic status [SES], perceived discrimination, neighbourhood disadvantage and control, family bonds, religiousness). We discover two ‘minority paradoxes’. Firstly, contrary to analyses using administrative data, both minorities have similar to lower self-reported crime rates compared to the majority group when age, sex, urbanization, SES and social desirability are controlled. Secondly, first-generation immigrants report fewer crimes than expected given their social disadvantage, thus indicating a notable ‘righteous migrant effect’.